Assessing the clinical probability of pulmonary embolism during pregnancy: The Pregnancy‐Adapted Geneva (PAG) score. (21st September 2021) - Robert‐Ebadi, Helia; Elias, Antoine; Sanchez, Olivier; Le Moigne, Emmanuelle; Schmidt, Jeannot; Le Gall, Catherine; Aujesky, Drahomir; Roy, Pierre‐Marie; Moumneh, Thomas; Chauleur, Céline; Rouyer, Frederic; Le Gal, Grégoire; et al.
Abstract: Background: The diagnosis of pulmonary embolism (PE) in pregnant women represents an ongoing challenge. As in the general population, the first step in pregnant women with suspected PE consists of assessing clinical pre‐test probability (PTP). However, no dedicated clinical decision rule has been developed in this population. Objective: To propose a new version of the Geneva score adapted to pregnant women with suspected PE. Methods: Data from a multicenter, prospective management outcome study including 395 women with suspected PE, in whom PTP was assessed using the Geneva score, were used. We first removed items which were present in none of the patients (cancer, age >65 years). Receiver operating characteristic (ROC) curve analysis was then performed for quantitative variables and the optimal threshold defined. The obtained Pregnancy‐Adapted Geneva Score (PAG Score) comprised seven items, including an age 40 years or older and a heart rate >110 beats per minute. Results: The PAG Score showed a high discriminative power to identify patients with a low, intermediate, or high PTP, associated with increasing prevalence of PE, 2.3%, 11.6%, and 61.5%, respectively. The ROC curves showed an area under the curve of 0.795 for the PAG Score compared to 0.684 for the Geneva score. Conclusion: In pregnant women with suspected PE, the PAG Score shows a high discriminative power to identify patients at low, intermediate, or high PTP. It has the strength of being a fully objective decision rule, is clinically relevant, easy to compute, and should now be tested in a prospective outcome study.